Catalytic cracking catalyst with mesopore-macropore structure as well as preparation method and application of catalytic cracking catalyst
By designing a bimodal mesomatous pore structure in the catalyst, combining materials such as mesoporous alumina and modified concave and convex rod soil, the problems of coke yield and heavy metal pollution in catalytic cracking are solved, and more efficient catalytic cracking and pollution reduction are achieved. .
Patent Information
- Application Number
- CN202310804997.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-30
- Publication Date
- 2025-01-03
AI Technical Summary
The existing catalytic cracking catalysts lack coke yield and resistance to heavy metal pollution in catalytic cracking of inferior raw oils, making it difficult to effectively reduce the amount of coke and capture heavy metals.
Using a catalyst with a bimodal mesomatous pore structure, the pore volume and specific surface area are controlled by adding mesoporous alumina, modified concave and convex rod soil, molecular sieve, binder and clay to the catalyst to form a rich pore structure of 20-100nm To promote macromolecular diffusion and heavy metal capture, and to optimize the structure of the catalyst through specific preparation methods and calcination conditions.
It significantly reduces the coke yield, improves the ability to resist heavy metal pollution, and enhances the conversion ability and coke selectivity of catalytic cracking poor-quality heavy oil molecules.
Smart Images

Figure CN119236996A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to a catalytic cracking catalyst with a medium- and macro-pore structure, and a preparation method and application thereof. Background Art
[0002] The pore structure is one of the important characteristics of catalytic cracking catalysts. It is a channel for the diffusion and mass transfer of hydrocarbon molecules and an important place for catalytic reactions. With the heavier quality of crude oil, the catalytic cracking unit gradually blends some residual oil fractions, whose molecular diameter is about 2.5-15nm. Larger hydrocarbon molecules are difficult to enter the micropores of the molecular sieve. The catalytic cracking catalyst is required to have a rich medium and large pore structure. At the same time, it also promotes the rapid diffusion of reactant molecules and product molecules, reduces the formation of coke precursors, and reduces the amount of coke produced by catalytic cracking, helping to achieve the goals of carbon peak and carbon neutrality.
[0003] CN105688977A discloses a method for preparing a catalytic cracking catalyst containing pseudo-boehmite. The method comprises mixing and stirring part of the pseudo-boehmite with a silicon-containing solution for more than 15 minutes to prepare a modified pseudo-boehmite A, mixing and slurrying the modified pseudo-boehmite A, the remaining pseudo-boehmite B, and clay to prepare a matrix slurry containing pseudo-boehmite, mixing the matrix slurry and the molecular sieve slurry, homogenizing, forming and drying, and ion exchange to obtain a catalytic cracking catalyst. The catalyst prepared by the method has a good anti-wear index, a high macropore volume, a strong heavy oil conversion ability, and a good coke selectivity, but when it is used in the catalytic cracking of inferior raw oil, its coke yield and resistance to heavy metal pollution need to be further improved. Summary of the invention
[0004] The purpose of the present disclosure is to provide a catalytic cracking catalyst with a medium- and macro-pore structure, a preparation method and an application thereof. The catalytic cracking catalyst has a bimodal medium- and macro-pore structure, good coke selectivity and strong resistance to heavy metal pollution.
[0005] In order to achieve the above-mentioned object, the first aspect of the present disclosure provides a catalytic cracking catalyst having a meso-macroporous structure, wherein the catalytic cracking catalyst contains 5-30 wt% of mesoporous alumina, 10-40 wt% of modified attapulgite, 20-50 wt% of molecular sieve, 5-40 wt% of binder and 0-30 wt% of clay, based on the total weight of the catalytic cracking catalyst;
[0006] The mesoporous alumina has a pseudo-boehmite structure, the total pore volume of the mesoporous alumina is 0.5-2.5 mL / g, the pore volume of 4-50 nm pores accounts for more than 80% of the total pore volume, and the specific surface area is 250-500 m 2 / g; the total pore volume of the modified attapulgite is more than 0.32mL / g, the pore volume of 10-100nm pores accounts for more than 80-98% of the total pore volume, and the specific surface area is 100m2 / g or more;
[0007] The catalytic cracking catalyst has a medium-large pore structure. The total pore volume of the catalytic cracking catalyst is above 0.250 mL / g, the pore volume of 4-20 nm pores accounts for 10-30% of the total pore volume, and the pore volume of 20-100 nm pores accounts for 30-60% of the total pore volume.
[0008] Optionally, the catalytic cracking catalyst contains 10-30 wt% of mesoporous alumina, 10-35 wt% of modified attapulgite, 25-45 wt% of molecular sieve, 10-35 wt% of binder and 2-25 wt% of clay.
[0009] Optionally, the total pore volume of the mesoporous alumina is 0.8-2 mL / g, the pore volume of 4-50 nm pores accounts for 85-95% of the total pore volume, and the specific surface area is 250-450 m 2 / g;
[0010] The total pore volume of the modified attapulgite is above 0.32-0.55 mL / g, the pore volume of 10-100 nm pores accounts for more than 80-98% of the total pore volume, and the specific surface area is 100-300 m 2 / g.
[0011] Optionally, the catalytic cracking catalyst has a bimodal meso-macroporous structure, the total pore volume of the catalytic cracking catalyst is 0.28-0.4 mL / g, the pore volume of 4-20 nm pores accounts for 15-30% of the total pore volume, and the pore volume of 20-100 nm pores accounts for 30-50% of the total pore volume.
[0012] Optionally, the molecular sieve is selected from NaY type molecular sieve, and the NaY type molecular sieve is one or more of high silicon-aluminum ratio Y zeolite, MFI type zeolite and Beta zeolite obtained after modification;
[0013] The binder is selected from one or more of aluminum sol, silica sol, silica-alumina sol, acidified pseudo-boehmite, aluminum phosphate sol and zirconium sol, preferably one or more of aluminum sol, silica sol and acidified pseudo-boehmite;
[0014] The clay is selected from one or more of kaolin, bentonite, montmorillonite, sepiolite, diatomaceous earth and rectorite, preferably kaolin.
[0015] The second aspect of the present disclosure provides a method for preparing the catalytic cracking catalyst provided in the first aspect of the present disclosure, the method comprising:
[0016] S1, mixing attapulgite and a first solvent, controlling the pH value of the obtained first mixture to be 1-5, stirring at 20-90° C. for 30-120 min, and taking out the solid to obtain the modified attapulgite;
[0017] S2, mixing the modified attapulgite, mesoporous alumina, clay, molecular sieve, binder and second solvent, controlling the pH value of the obtained second mixture to be 2-5, and then drying and calcining.
[0018] Optionally, step S1 comprises: mixing the attapulgite and the first solvent in a weight ratio of 1:(5-20), and adjusting the pH value of the first mixture to 1.5-4 using an acid solution;
[0019] The acid solution contains organic acid and / or inorganic acid; the organic acid is selected from one or more of oxalic acid, acetic acid and citric acid, and the inorganic acid is selected from one or more of hydrochloric acid, nitric acid, sulfuric acid, phosphoric acid, ammonium sulfate and ammonium chloride.
[0020] Optionally, step S2 includes:
[0021] SS1, mixing the modified attapulgite, the mesoporous alumina, the clay, and the second solvent to obtain a third mixture with a solid content of 10-50 wt %;
[0022] SS2. Mix the third mixture, the molecular sieve and the binder to obtain a second mixture with a solid content of 10-50 wt %, control the pH value of the obtained second mixture to be 2-5, and then dry and calcine.
[0023] Optionally, the drying conditions include: a temperature of 80-200°C;
[0024] The calcination conditions include: a temperature of 400-650° C. and a time of 1-5 hours.
[0025] A third aspect of the present disclosure provides an application of the catalytic cracking catalyst with a medium- and macro-pore structure provided by the first aspect of the present disclosure in the catalytic cracking of inferior crude oil.
[0026] Optionally, the catalytic cracking conditions include: temperature of 450-560° C., time of 1-3 s, and catalyst-oil mass ratio of 3-10.
[0027] Through the above technical scheme, the catalytic cracking catalyst disclosed in the present invention has a bimodal macroporous structure, which has the following advantages: it has a rich 20-100nm pore structure mainly from modified attapulgite, and has fewer acid centers, which is conducive to the diffusion of inferior heavy oil molecules and the inhibition of coking, while capturing heavy metals to avoid the destruction of heavy metals to the active components of molecular sieves; the 4-20nm pore structure mainly comes from mesoporous alumina, and has moderate acid centers, which is conducive to the conversion of macromolecules to medium molecules. The catalyst disclosed in the present invention is suitable for the conversion of inferior heavy oil molecules and has strong resistance to heavy metal pollution.
[0028] Other features and advantages of the present disclosure will be described in detail in the following detailed description. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] The accompanying drawings are used to provide a further understanding of the present disclosure and constitute a part of the specification. Together with the following specific embodiments, they are used to explain the present disclosure but do not constitute a limitation of the present disclosure. In the accompanying drawings:
[0030] Figure 1 This is a pore size distribution diagram of the catalytic cracking catalyst prepared in Example 1 of the present disclosure.
[0031] Figure 2 This is the pore size distribution diagram of the modified attapulgite prepared in Example 1 of the present disclosure.
[0032] Figure 3 It is the pore size distribution diagram of the catalytic cracking catalyst prepared in Comparative Example 1 of the present disclosure. DETAILED DESCRIPTION
[0033] The specific implementation of the present disclosure is described in detail below in conjunction with the accompanying drawings. It should be understood that the specific implementation described herein is only used to illustrate and explain the present disclosure, and is not used to limit the present disclosure.
[0034] The first aspect of the present disclosure provides a catalytic cracking catalyst having a meso-macroporous structure, wherein the catalytic cracking catalyst contains 5-30 wt% of mesoporous alumina, 10-40 wt% of modified attapulgite, 20-50 wt% of molecular sieve, 5-40 wt% of binder and 0-30 wt% of clay, based on the total weight of the catalytic cracking catalyst;
[0035] The mesoporous alumina has a pseudo-boehmite structure, the total pore volume of the mesoporous alumina is 0.5-2.5 mL / g, the pore volume of 4-50 nm pores accounts for more than 80% of the total pore volume, and the specific surface area is 250-500 m 2 / g; the total pore volume of the modified attapulgite is 0.32 mL / g or more, the pore volume of 10-100 nm pores accounts for 80-98% of the total pore volume, and the specific surface area is 100 m 2 / g or more;
[0036] The catalytic cracking catalyst has a medium-large pore structure. The total pore volume of the catalytic cracking catalyst is above 0.250 mL / g, the pore volume of 4-20 nm pores accounts for 10-30% of the total pore volume, and the pore volume of 20-100 nm pores accounts for 30-60% of the total pore volume.
[0037] The catalyst disclosed in the present invention has a medium- and large-pore structure with bimodal distributions at 4-20nm and 20-100nm, which is beneficial to the diffusion and pre-cracking of macromolecules of catalytic cracking inferior crude oil, which is beneficial to reducing the formation of coke and can capture heavy metals in the crude oil.
[0038] The range values expressing sizes in the present disclosure all include the endpoint values at both ends. For example, in "the pore volume of 4-50nm pores accounts for more than 80% of the total pore volume", 4-50nm pores refer to pores with a pore diameter ranging from 4nm to 50nm; for another example, "the pore volume of 10-100nm pores accounts for 80-98% of the total pore volume", 10-100nm pores refer to pores with a pore diameter ranging from 10nm to 100nm.
[0039] In a specific embodiment of the present disclosure, the catalytic cracking catalyst contains 10-30 wt% of mesoporous alumina, 15-35 wt% of modified attapulgite, 25-45 wt% of molecular sieve, 10-35 wt% of binder and 2-25 wt% of clay.
[0040] In a specific embodiment of the present disclosure, the total pore volume of the mesoporous alumina is 0.8-2 mL / g, the pore volume of 4-50 nm pores accounts for 85-95% of the total pore volume, and the specific surface area is 250-450 m 2 / g; the total pore volume of the modified attapulgite is 0.32-0.55mL / g or more, the pore volume of 10-100nm pores accounts for more than 80-98% of the total pore volume, and the specific surface area is 100-300m 2 / g.
[0041] In a specific embodiment of the present disclosure, the catalytic cracking catalyst has a bimodal meso-macroporous structure, the total pore volume of the catalytic cracking catalyst is 0.28-0.4 mL / g, the pore volume of 4-20 nm pores accounts for 15-30% of the total pore volume, and the pore volume of 20-100 nm pores accounts for 30-50% of the total pore volume.
[0042] In a specific embodiment of the present disclosure, the molecular sieve is one or more of a Y-type molecular sieve, an MFI-type zeolite and a Beta zeolite, and the Y-type molecular sieve may be a Y zeolite obtained by modifying a NaY-type molecular sieve. The Y zeolite obtained by modifying the NaY-type molecular sieve may include but is not limited to HY, REY, REHY, USY and REUSY.
[0043] In a specific embodiment of the present disclosure, the binder is selected from one or more of aluminum sol, silica sol, silica-alumina sol, acidified pseudo-boehmite, aluminum phosphate sol and zirconium sol, preferably one or more of aluminum sol, silica sol and acidified pseudo-boehmite.
[0044] In a specific embodiment of the present disclosure, the clay is selected from one or more of kaolin, bentonite, montmorillonite, sepiolite, diatomaceous earth and rectorite, preferably kaolin.
[0045] The second aspect of the present disclosure provides a method for preparing the catalytic cracking catalyst provided in the first aspect of the present disclosure, the method comprising: S1, mixing attapulgite and a first solvent, controlling the pH value of the obtained first mixture to be 1-5, stirring at 20-90°C for 30-120min, and taking out the solid to obtain the modified attapulgite; S2, mixing the modified attapulgite, mesoporous alumina, clay, molecular sieve, binder and a second solvent, controlling the pH value of the obtained second mixture to be 2-5, and then drying and calcining.
[0046] The present disclosure does not impose any specific restrictions on the method of removing the solid, for example, filtration, centrifugal separation, etc. The first solvent and the second solvent in the present disclosure can be independently selected from deionized water and / or decationized water.
[0047] The method disclosed in the present invention can prepare a catalytic cracking catalyst having a bimodal distribution of meso-macropore structure, and the catalyst has a good anti-wear index, a low coke yield, and a strong ability to resist heavy metal pollution.
[0048] In the present disclosure, the mesoporous alumina can be purchased as a commercial product or prepared in the following manner, but is not limited to the following preparation method: (1) mixing an aluminate solution with an alkaline solution for neutralization reaction to obtain a neutralized slurry; (2) adjusting the pH value of the neutralized slurry to 10-10.5; (3) aging the neutralized slurry after adjusting the pH value at 50-70°C for 4-48h to obtain an aged slurry; (4) filtering and washing the aged slurry, and drying the obtained filter cake at 80-150°C.
[0049] In a specific embodiment of the present disclosure, the aluminate solution in step (1) is selected from one or more of aluminum sulfate, sodium aluminate, aluminum nitrate and aluminum chloride, preferably aluminum sulfate; the alkaline solution is selected from one or more of sodium hydroxide, sodium carbonate and sodium aluminate, preferably sodium aluminate solution; the neutralized slurry has a pH value of 8.5-9.5, a temperature of 45-75°C, and a residence time of 5-30 min.
[0050] In a specific embodiment of the present disclosure, step (2) comprises: adjusting the pH value of the neutralized slurry to 10-10.5 using an aluminum-free alkaline solution, wherein the aluminum-free alkaline solution includes but is not limited to one or more of sodium hydroxide, sodium carbonate, sodium bicarbonate, and ammonia water, preferably sodium carbonate solution.
[0051] In a specific embodiment of the present disclosure, step S1 comprises: after mixing the attapulgite and the first solvent in a weight ratio of 1:(5-20), adjusting the pH value of the first mixture to 1.5-4 using an acid solution. The acid solution used in the present disclosure is well known to those skilled in the art, and the acid solution may contain an organic acid and / or an inorganic acid; the organic acid is selected from one or more of oxalic acid, acetic acid and citric acid, and the inorganic acid may be selected from one or more of hydrochloric acid, nitric acid, sulfuric acid, phosphoric acid, ammonium sulfate and ammonium chloride.
[0052] In a specific embodiment of the present disclosure, step S2 includes: SS1, mixing the modified attapulgite, the mesoporous alumina, the clay, and the second solvent to obtain a third mixture with a solid content of 10-50% by weight; SS2, mixing the third mixture, the molecular sieve, and the binder to obtain a second mixture with a solid content of 10-50% by weight, and drying and calcining the obtained second mixture after controlling the pH value to 2.5-4.5. The present disclosure does not specifically limit the mixing method, for example, it can be a stirring mixing method, and the stirring mixing time is also not specifically limited, for example, it can be 30-360 minutes.
[0053] The method disclosed in the present invention adopts a step-by-step mixing method, and a catalytic cracking catalyst with better catalytic activity can be prepared. The use of the catalyst in the catalytic cracking of inferior crude oil is beneficial to further reduce the coke yield, and the catalyst has better resistance to heavy metal pollution.
[0054] In a specific embodiment of the present disclosure, the drying conditions include: temperature of 80-200°C; preferably, temperature of 100-180°C; the calcining conditions include: temperature of 400-650°C, time of 1-5 hours; preferably, temperature of 450-550°C, time of 1-3 hours.
[0055] A third aspect of the present disclosure provides an application of the catalytic cracking catalyst with a medium- and macro-pore structure provided by the first aspect of the present disclosure in the catalytic cracking of inferior crude oil.
[0056] The low-quality feedstock oil described in the present disclosure has a carbon residue value of 4.0 m% or more, and a total metal content of Fe, Ni and V of 15 ppm or more.
[0057] In a specific embodiment of the present disclosure, the catalytic cracking conditions include: temperature of 450-560°C, time of 1-3s, catalyst-oil mass ratio of 3-10; preferably, temperature of 500-530°C, time of 1-2.5s, catalyst-oil mass ratio of 4-9.
[0058] The present disclosure is further illustrated below by way of examples, but the present disclosure is not limited thereby.
[0059] The raw materials used in the preparation of the catalyst are as follows: kaolin solid content of 76 wt%; aluminum oxide content in aluminum sol of 22.0 wt%; SiO2 content in silica sol of 30.0 wt%; acidified pseudo-boehmite solid content of 12.0 wt%, acidified with hydrochloric acid, the molar ratio of acid (HCl) to aluminum oxide during acidification is 0.20. The rare earth ultra-stable Y zeolite REUSY used has a solid content of 85.0 wt% and a unit cell constant of In terms of weight percentage, the Na2O content is 1.6% and the RE2O3 content is 12.0%.
[0060] The preparation method of the mesoporous pseudo-boehmite used in Examples 1-7 of the present invention is as follows: (1) an aluminum sulfate solution with a concentration of 50.0 g / L in terms of alumina and a sodium aluminate solution with a concentration of 220 g / L in terms of oxides Al2O3 and 227 g / L Na2O are added in parallel to a neutralization reactor for neutralization reaction at a temperature of 65°C and a residence time of 15 min to obtain a neutralized slurry with a pH value of 8.8; (2) a Na2CO3 solution is added to the slurry after the neutralization reaction to further adjust the pH value of the neutralized slurry to 10.1; (3) the neutralized slurry obtained in step (2) is heated to 50°C and kept at a constant temperature for 6 hours for aging to obtain an aged slurry; (4) the aged slurry is filtered through a vacuum filter and washed with 90°C deionized water to obtain a filter cake; the filter cake is spray-dried to obtain the mesoporous pseudo-boehmite. The solid content of the mesoporous pseudo-boehmite is 68.0% by weight and the BET specific surface area is 385 m 2 / g, the total pore volume is 0.98mL / g, and the pore volume of 4-50nm accounts for 86% of the total pore volume.
[0061] The preparation method of mesoporous pseudo-boehmite used in Example 8 of the present invention is as follows: (1) Aluminum sulfate solution with a concentration of 50.0 g / L in terms of aluminum oxide and sodium aluminate solution with a concentration of 220 g / L in terms of oxide Al2O3 and 227 g / L in terms of Na2O are added to a neutralization reactor in parallel for neutralization reaction. The reaction temperature is 55°C and the residence time is 20 min. The pH value of the obtained neutralized slurry is 9.5; (2) Na2CO3 solution is added to the slurry after the neutralization reaction to further adjust the pH value of the neutralized slurry to 10.5; (3) The neutralized slurry obtained in step (2) is heated to 65°C and kept at a constant temperature for 4 hours for aging to obtain an aged slurry; (4) The aged slurry is filtered with a vacuum filter and washed with 90°C deionized water to obtain a filter cake; the filter cake is spray-dried to obtain mesoporous pseudo-boehmite. The BET specific surface area of mesoporous pseudo-boehmite is 350 m 2 / g, the total pore volume is 0.55mL / g, and the pore volume of 4-50nm accounts for 82% of the total pore volume.
[0062] The solid content of conventional pseudo-boehmite is 73.0% by weight, and the BET specific surface area is 341m 2 / g, the total pore volume is 0.32mL / g, and the pore volume of 4-50nm accounts for 23% of the total pore volume.
[0063] The solid content of attapulgite is 79.8% by weight and the BET specific surface area is 98m 2 / g, the pore volume is 0.30mL / g, and the pore volume of 10-100nm accounts for 75% of the total pore volume.
[0064] The analysis and evaluation methods are described as follows:
[0065] Specific surface area and pore volume analysis: The ASAP 2405N V1.01 automatic adsorption instrument from Micromeritics, USA, was used, and the low temperature static nitrogen adsorption capacity method was used. The sample was heated to 1.33×10 -2 Pa, vacuum degassing at 300 ° C for 4 hours, using N2 as the adsorption medium, and measuring the adsorption-desorption isotherm of the sample at 77.4 K. The specific surface area of the sample was calculated according to the BET formula, and the volume of N2 adsorbed by the sample when the relative pressure p / p0 = 0.98 was measured and converted into liquid nitrogen volume, i.e., the total pore volume. The micropore volume was calculated according to the t-plot method, and the pore volumes of 4-50nm, 10-100nm, 4-20nm, and 20-100nm pores were all calculated using the BJH desorption branch.
[0066] Catalyst strength: put a certain amount of catalyst into a fixed device and blow it for 5 hours under a constant airflow. Except for the first hour, the average wear percentage in the last four hours is called the catalyst wear index, and the unit is % per hour. The method and standard are: air lift method Q / SYLS0518-2002.
[0067] Example 1
[0068] S1. 376 g of attapulgite and deionized water were mixed and stirred in a mass ratio of 1:5, and 36 wt % hydrochloric acid was added to adjust the pH value of the slurry to 3.0. The mixture was stirred at 60° C. for 90 min, filtered, and dried at 120° C. to obtain modified attapulgite, which was recorded as AT-1 and had a pore size distribution as shown in FIG. Figure 2 shown.
[0069] According to analysis, the specific surface area of modified attapulgite is 128m 2 / g, the total pore volume is 0.38mL / g, and the pore volume of 10-100nm accounts for 83% of the total pore volume.
[0070] S2, 79 grams of kaolin, 376 grams of modified attapulgite (AT-1) prepared in step S1, 147 grams of medium-porous pseudo-boehmite and 600 grams of decationized water are added to a beating tank and beaten for 120 minutes to obtain a slurry with a solid content of 38.3%, 818 grams of aluminum sol and 1029 grams of REUSY molecular sieve slurry (including 424 grams of REUSY molecular sieve and a slurry solid content of 35 weight%) are added to the slurry, stirred for 60 minutes, and 36 weight% hydrochloric acid is added to adjust the slurry pH to 3.5, and the obtained mixed slurry has a solid content of 32.8 weight%, and then the obtained slurry is spray-dried and formed, and calcined at 500°C for 1 hour to obtain the catalyst C1 provided in the present disclosure, whose composition and characteristic parameters are shown in Table 1, and the same as the following embodiments, and its pore size distribution is as follows Figure 1 shown.
[0071] Example 2
[0072] S1. 313 g of attapulgite and deionized water were mixed and stirred evenly in a mass ratio of 1:8, 65 wt % nitric acid was added to adjust the pH value of the slurry to 2.0, stirred at 80° C. for 60 min, filtered, and a filter cake was obtained, which was recorded as modified attapulgite AT-2.
[0073] According to analysis, the specific surface area of modified attapulgite is 136m 2 / g, the total pore volume is 0.42mL / g, and the pore volume of 10-100nm accounts for 88% of the total pore volume.
[0074] S2. Add 26 grams of kaolin, 313 grams of modified attapulgite (AT-2) prepared in step S1, 221 grams of medium-porous pseudo-boehmite and 579 grams of decationized water into a slurry tank and slurry for 90 minutes to obtain a slurry with a solid content of 36.9%. Add 1000 grams of aluminum sol and 1029 grams of REUSY molecular sieve slurry (including 424 grams of REUSY molecular sieve and a slurry solid content of 35 weight %) to the slurry, stir for 90 minutes, add nitric acid with a concentration of 65 weight % to adjust the slurry pH to 3.2, and the obtained mixed slurry has a solid content of 31.6 weight %. Then, the obtained slurry is spray dried and formed, and calcined at 550°C for 1 hour to obtain the catalyst C2 provided in the present disclosure.
[0075] Example 3
[0076] S1. Mix 188 grams of attapulgite and deionized water in a mass ratio of 1:10 and stir evenly, add 36% by weight hydrochloric acid to adjust the pH value of the slurry to 2.8, stir at room temperature for 60 minutes, and filter; mix the filter cake with deionized water in a mass ratio of 1:10, adjust the pH value of the slurry to 3.0 with 5% by weight dilute hydrochloric acid, stir at 60°C for 60 minutes, and filter the filter cake obtained as modified attapulgite AT-3.
[0077] According to analysis, the specific surface area of modified attapulgite is 129m 2 / g, the total pore volume is 0.39mL / g, and the pore volume of 10-100nm accounts for 82% of the total pore volume.
[0078] S2. Add 53 g of kaolin, 294 g of medium-porous pseudo-boehmite and 1000 g of aluminum sol to 644 g of cationic water, and stir at room temperature for 90 minutes; then add 188 g of modified attapulgite (AT-3) prepared in step S1 and 1029 g of REUSY molecular sieve slurry (including 424 g of REUSY molecular sieve and 35 wt % solid content of slurry) to the above slurry, stir for 120 min, add 36 wt % hydrochloric acid to adjust the slurry pH to 3.8, the solid content of the obtained mixed slurry is 31.2 wt %, and then the obtained slurry is spray dried and formed, and calcined at 450°C for 5 hours to obtain the catalyst C3 provided in the present disclosure.
[0079] Example 4
[0080] S1. Mix 188 grams of attapulgite and deionized water in a mass ratio of 1:6 and stir evenly, add 36% by weight hydrochloric acid to adjust the pH value of the slurry to 3.5, stir at 40°C for 60 minutes, and filter; mix the filter cake with deionized water in a mass ratio of 1:6, adjust the pH value of the slurry to 3.0 with 20% by weight phosphoric acid, stir at 40°C for 60 minutes, filter and obtain the filter cake, dry it at 150°C, and obtain modified attapulgite, recorded as AT-4.
[0081] According to analysis, the specific surface area of modified attapulgite is 126m 2 / g, the total pore volume is 0.38mL / g, and the pore volume of 10-100nm accounts for 83% of the total pore volume.
[0082] S2. Add 1029 g of REUSY molecular sieve slurry (including 424 g of REUSY molecular sieve and 35 wt% solid content of slurry), 53 g of kaolin, 188 g of modified attapulgite (AT-4) prepared in step S1, and 368 g of medium-porous pseudo-boehmite into a slurrying tank and slurry for 180 min. Then add 682 g of aluminum sol and continue stirring for 90 min. Finally, add 167 g of silica sol and stir for 30 min. Add 36 wt% hydrochloric acid to adjust the pH of the slurry to 3.6. The solid content of the obtained mixed slurry is 38.6 wt%. Then, the obtained slurry is spray-dried and formed, and calcined at 600°C for 1 hour to obtain the catalyst C4 provided in the present disclosure.
[0083] Example 5
[0084] S1. 251 g of attapulgite and deionized water were mixed and stirred in a mass ratio of 1:12, 36 wt % hydrochloric acid was added to adjust the pH value of the slurry to 4.0, stirred at 90° C. for 30 min, filtered, and then dried at 120° C. to obtain modified attapulgite recorded as AT-5.
[0085] According to analysis, the specific surface area of modified attapulgite is 132m 2 / g, the total pore volume is 0.41mL / g, and the pore volume of 10-100nm accounts for 86% of the total pore volume.
[0086] S2. Add 857 grams of REUSY molecular sieve slurry (including 353 grams of REUSY molecular sieve and 35 weight percent solid content of the slurry), 132 grams of kaolin, 251 grams of modified attapulgite (AT-5) prepared in step S1, and 294 grams of medium-porous pseudo-boehmite into a slurrying tank and slurry for 120 minutes. Then add 909 grams of aluminum sol and continue stirring for 60 minutes. Add 36 weight percent hydrochloric acid to adjust the slurry pH to 4.0. The solid content of the obtained mixed slurry is 40 weight percent. Then, the obtained slurry is spray dried to form, and calcined at 450°C for 3 hours to obtain the catalyst C5 provided in the present disclosure.
[0087] Example 6
[0088] S1. Mix 276 g of attapulgite and deionized water in a mass ratio of 1:15 and stir evenly, add 30 wt % oxalic acid to adjust the pH value of the slurry to 2.0, stir at 60° C. for 60 min, filter, and dry the filter cake at 100° C. to obtain modified attapulgite, recorded as AT-6.
[0089] After analysis, the specific surface area of the attapulgite is 128m 2 / g, the total pore volume is 0.38mL / g, and the pore volume of 10-100nm accounts for 84% of the total pore volume.
[0090] S2. Add 1238 g of decationized water, 276 g of modified attapulgite (AT-6) prepared in step S1, and 441 g of medium-porous pseudo-boehmite into a slurrying tank and slurry for 180 min. Then add 1045 g of aluminum sol and continue stirring for 60 min. Finally, add 714 g of REUSY molecular sieve slurry (including 294 g of REUSY molecular sieve and 35 wt % solid content of slurry) and continue stirring for 60 min. Add 30 wt % oxalic acid to adjust the slurry pH to 4.2. The solid content of the obtained mixed slurry is 26 wt %. Then, the obtained slurry is spray dried and formed, and calcined at 500° C. for 2 hours to obtain the catalyst C6 provided in the present disclosure.
[0091] Example 7
[0092] A catalytic cracking catalyst was prepared by the same method as in Example 1, except that in step S2, 382 g of kaolin, 125 g of modified attapulgite (AT-1) prepared in step S1, 103 g of medium-porous pseudo-boehmite and 600 g of decationized water were added to a slurrying tank and slurried for 120 min to obtain a slurry with a solid content of 38%. 818 g of aluminum sol and 1029 g of REUSY molecular sieve slurry (including 424 g of REUSY molecular sieve and a slurry solid content of 35 wt %) were added to the slurry, stirred for 60 min, and 36 wt % hydrochloric acid was added to adjust the slurry pH to 3.8. The solid content of the obtained mixed slurry was 32.7 wt %. The obtained slurry was then spray dried and formed, and calcined at 500° C. for 1 hour to obtain the catalyst C7 provided in the present disclosure.
[0093] Example 8
[0094] The catalytic cracking catalyst was prepared by the same method as in Example 1, except that the BET specific surface area of the mesoporous pseudo-boehmite was 350 m 2 / g, the total pore volume is 0.55mL / g, and the pore volume of 4-50nm accounts for 82% of the total pore volume, thereby obtaining the catalyst C8 provided by the present disclosure.
[0095] Comparative Example 1
[0096] The catalytic cracking catalyst was prepared by the same method as in Example 2, except that this comparative example did not contain attapulgite, and conventional pseudo-boehmite was used instead of the mesoporous pseudo-boehmite.
[0097] 355 g of kaolin, 205 g of conventional pseudo-boehmite and 600 g of decationized water were added to a beating tank and beaten for 120 min to obtain a slurry with a solid content of 36.2%. 1000 g of aluminum sol and 1029 g of REUSY molecular sieve slurry (including 424 g of REUSY molecular sieve and a slurry solid content of 35 wt %) were added to the slurry, stirred for 60 min, and 65 wt % nitric acid was added to adjust the slurry pH to 3.5. The obtained mixed slurry had a solid content of 31.4 wt %. The obtained slurry was then spray dried and formed, and calcined at 550° C. for 1 hour to obtain the catalyst DC1 provided by the present disclosure, whose pore size distribution is as follows: Figure 3 shown.
[0098] Comparative Example 2
[0099] The catalytic cracking catalyst was prepared by the same method as in Example 2, except that the catalyst of this comparative example did not contain attapulgite.
[0100] 355 g of kaolin, 221 g of medium-porous pseudo-boehmite and 600 g of decationized water are added to a beating tank and beaten for 120 min to obtain a slurry with a solid content of 35.7%. 1000 g of aluminum sol and 1029 g of REUSY molecular sieve slurry (including 424 g of REUSY molecular sieve and a slurry solid content of 35 wt%) are added to the slurry, stirred for 60 min, and 65 wt% nitric acid is added to adjust the slurry pH to 2.8. The solid content of the obtained mixed slurry is 31.2 wt%. The obtained slurry is then spray-dried and formed, and calcined at 550°C for 1 hour to obtain the catalyst DC2 provided in the present disclosure.
[0101] Comparative Example 3
[0102] The catalytic cracking catalyst was prepared by the same method as in Example 2, except that conventional pseudo-boehmite was used instead of mesoporous pseudo-boehmite in this comparative example.
[0103] 26 g of kaolin, 205 g of conventional pseudo-boehmite, 313 g of modified attapulgite (AT-2) prepared in step S1 and 379 g of decationized water are added to a slurrying tank and slurried for 120 min to obtain a slurry with a solid content of 37.4%. 1000 g of aluminum sol and 1029 g of REUSY molecular sieve slurry (including 424 g of REUSY molecular sieve and a slurry solid content of 35 wt %) are added to the slurry, stirred for 60 min, and 65 wt % nitric acid is added to adjust the slurry pH to 3.2. The solid content of the obtained mixed slurry is 38 wt %. The obtained slurry is then spray dried and formed, and calcined at 550° C. for 1 hour to obtain the catalyst DC3 provided in the present disclosure.
[0104] Table 1 Composition and physicochemical properties of catalysts
[0105]
[0106]
[0107]
[0108] Catalysts C1-C8 prepared in Examples 1-8 and catalysts DC1-DC3 prepared in Comparative Examples 1-3 were pre-impregnated and contaminated by the Michael method. The contaminated heavy metals were 5000μg / g iron, 5000μg / g nickel and 3000μg / g vanadium. That is, vanadium cyclopentaneate was used as the vanadium source, nickel cyclopentaneate was used as the nickel source, iron cyclopentaneate was used as the iron source, and toluene was used as the solvent to prepare a metal-containing solution. The catalyst was impregnated in the metal-containing solution, then dried, and then calcined at about 600°C to remove organic matter. The contaminated catalyst was aged at 780°C and 100% steam for 4h and then evaluated on a small fixed fluidized bed (ACE) device. The properties of the reaction raw oil are shown in Table 2, the catalyst-oil weight ratio is 6.0, the sample loading is 9g, the reaction temperature is 500°C, and the evaluation results are listed in Table 3.
[0109] Conversion rate = gasoline yield + liquefied gas yield + dry gas yield + coke yield;
[0110] Coke selectivity = coke yield / conversion rate × 100;
[0111] Coke factor (also called coke generation factor) = coke yield × (1-conversion rate) / conversion rate × 100.
[0112] Table 2 Raw oil properties
[0113]
[0114] Table 3 Evaluation results
[0115]
[0116]
[0117] Comparative Example 1 Comparative Example 2 Comparative Example 3 Catalyst name DC1 DC2 DC3 Product distribution, % Dry gas 2.91 2.88 2.89 Liquefied gas 14.63 13.89 14.19 gasoline 45.45 49.08 47.22 diesel fuel 15.13 15.38 16.21 heavy oil 10.90 9.69 10.45 Coke 10.98 9.08 9.04 Conversion rate, % 73.97 74.93 73.34 Coke selectivity, % 14.84 12.12 12.33 Coke Factor 2.86 2.28 2.41
[0118] As shown in Table 1 and the accompanying drawings, compared with Comparative Examples 1 to 3, the total pore volume and the proportion of 4-20nm and 20-100nm pores of the catalysts prepared in Examples 1 to 8 are significantly increased. The results in Table 3 show that the heavy oil yield is low, the coke yield is reduced, the coke selectivity is significantly improved, and the coke generation factor is reduced. It can be seen that the catalytic cracking catalyst prepared in the present disclosure has a rich bimodal meso-macroporous structure, and the catalyst acidity is suitable, so that it has excellent heavy oil cracking ability and good coke selectivity, and at the same time has good resistance to heavy metal pollution.
[0119] The preferred embodiments of the present disclosure are described in detail above in conjunction with the accompanying drawings; however, the present disclosure is not limited to the specific details in the above embodiments. Within the technical concept of the present disclosure, a variety of simple modifications can be made to the technical solution of the present disclosure, and these simple modifications all fall within the protection scope of the present disclosure.
[0120] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present disclosure will not further describe various possible combinations.
[0121] In addition, various embodiments of the present disclosure may be arbitrarily combined, and as long as they do not violate the concept of the present disclosure, they should also be regarded as the contents disclosed by the present disclosure.
Claims
1. A catalytic cracking catalyst having a meso-macroporous structure, which comprises, based on the total weight of the catalytic cracking catalyst, 5-30 wt% of mesoporous alumina, 10-40 wt% of modified attapulgite, 20-50 wt% of molecular sieve, 5-40 wt% of binder and 0-30 wt% of clay; The mesoporous alumina has a pseudo-boehmite structure, the total pore volume of the mesoporous alumina is 0.5-2.5 mL / g, the pore volume of 4-50 nm pores accounts for more than 80% of the total pore volume, and the specific surface area is 250-500 m 2 / g; the total pore volume of the modified attapulgite is 0.32mL / g or more, the pore volume of 10-100nm pores accounts for 80-98% of the total pore volume, and the specific surface area is 100m 2 / g or more; The catalytic cracking catalyst has a medium-large pore structure. The total pore volume of the catalytic cracking catalyst is above 0.250 mL / g, the pore volume of 4-20 nm pores accounts for 10-30% of the total pore volume, and the pore volume of 20-100 nm pores accounts for 30-60% of the total pore volume.
2. The catalytic cracking catalyst according to claim 1, wherein The catalytic cracking catalyst contains 10-30 weight percent of mesoporous alumina, 10-35 weight percent of modified attapulgite, 25-45 weight percent of molecular sieve, 10-35 weight percent of binder and 2-25 weight percent of clay.
3. The catalytic cracking catalyst according to claim 1, wherein The total pore volume of the mesoporous alumina is 0.8-2 mL / g, the pore volume of 4-50 nm pores accounts for 85-95% of the total pore volume, and the specific surface area is 250-450 m 2 / g; The total pore volume of the modified attapulgite is above 0.32-0.55 mL / g, the pore volume of 10-100 nm pores accounts for 80-98% of the total pore volume, and the specific surface area is 100-300 m 2 / g.
4. The catalytic cracking catalyst according to claim 1, wherein The catalytic cracking catalyst has a bimodal macroporous structure. The total pore volume of the catalytic cracking catalyst is 0.28-0.4 mL / g, the pore volume of 4-20 nm pores accounts for 15-30% of the total pore volume, and the pore volume of 20-100 nm pores accounts for 30-50% of the total pore volume.
5. The catalytic cracking catalyst according to claim 1, wherein The molecular sieve is selected from NaY type molecular sieve, and the NaY type molecular sieve is one or more of the modified high silicon-aluminum ratio Y zeolite, MFI type zeolite and Beta zeolite; The binder is selected from one or more of aluminum sol, silica sol, silica-alumina sol, acidified pseudo-boehmite, aluminum phosphate sol and zirconium sol, preferably one or more of aluminum sol, silica sol and acidified pseudo-boehmite; The clay is selected from one or more of kaolin, bentonite, montmorillonite, sepiolite, diatomaceous earth and rectorite, preferably kaolin.
6. A method for preparing the catalytic cracking catalyst according to any one of claims 1 to 5, the method comprising: S1, mixing attapulgite and a first solvent, controlling the pH value of the obtained first mixture to be 1-5, stirring at 20-90° C. for 30-120 min, and taking out the solid to obtain the modified attapulgite; S2, mixing the modified attapulgite, mesoporous alumina, clay, molecular sieve, binder and second solvent, controlling the pH value of the obtained second mixture to be 2-5, and then drying and calcining.
7. The method according to claim 6, wherein: Step S1 comprises: mixing the attapulgite and the first solvent in a weight ratio of 1:(5-20), and adjusting the pH value of the first mixture to 1.5-4 using an acid solution; The acid solution contains organic acid and / or inorganic acid; the organic acid is selected from one or more of oxalic acid, acetic acid and citric acid, and the inorganic acid is selected from one or more of hydrochloric acid, nitric acid, sulfuric acid, phosphoric acid, ammonium sulfate and ammonium chloride.
8. The method according to claim 6, wherein: Step S2 includes: SS1, mixing the modified attapulgite, the mesoporous alumina, the clay, and the second solvent to obtain a third mixture with a solid content of 10-50 wt %; SS2. Mix the third mixture, the molecular sieve and the binder to obtain a second mixture with a solid content of 10-50 wt %, control the pH value of the obtained second mixture to be 2.5-4.5, and then dry and calcine.
9. The method according to claim 6, wherein: The drying conditions include: a temperature of 80-200°C; The calcination conditions include: a temperature of 400-650° C. and a time of 1-5 hours.
10. Use of the catalytic cracking catalyst having a medium- and macro-pore structure according to any one of claims 1 to 5 in the catalytic cracking of inferior crude oil.
11. The use according to claim 10, wherein: The catalytic cracking conditions include: temperature of 450-560° C., time of 1-3 s, and catalyst-oil mass ratio of 3-10.
